Transplant of organs from donors with positive SARS‐CoV‐2 nucleic acid testing: A report from the organ procurement and transplantation network ad hoc disease transmission advisory committee. Issue 1 (24th January 2023) - Goldman, Jason D.; Pouch, Stephanie M.; Woolley, Ann E.; Booker, Sarah E.; Jett, Courtney T.; Fox, Cole; Berry, Gerald J.; Dunn, Kelly E.; Ho, Chak‐Sum; Kittleson, Michelle; Lee, Dong Heun; Levine, Deborah J.; et al.
Abstract: Background: Decisions to transplant organs from severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) nucleic acid test‐positive (NAT+) donors must balance risk of donor‐derived transmission events (DDTE) with the scarcity of available organs. Methods: Organ Procurement and Transplantation Network (OPTN) data were used to compare organ utilization and recipient outcomes between SARS‐CoV‐2 NAT+ and NAT– donors. NAT+ was defined by either a positive upper or lower respiratory tract (LRT) sample within 21 days of procurement. Potential DDTE were adjudicated by OPTN Disease Transmission Advisory Committee. Results: From May 27, 2021 (date of OTPN policy for required LRT testing of lung donors) to January 31, 2022, organs were recovered from 617 NAT+ donors from all OPTN regions and 53 of 57 (93%) organ procurement organizations. NAT+ donors were younger and had higher organ quality scores for kidney and liver. Organ utilization was lower for NAT+ donors compared to NAT– donors. A total of 1241 organs (776 kidneys, 316 livers, 106 hearts, 22 lungs, and 21 other) were transplanted from 514 NAT+ donors compared to 21 946 organs from 8853 NAT– donors. Medical urgency was lower for recipients of NAT+ liver and heart transplants. The median waitlist time was longer for liver recipients of NAT+ donors. The match run sequence number for final acceptor was higher for NAT+ donors for all organ types. Outcomes for hospital length of stay, 30‐day mortality, and 30‐day graft loss were similar for all organ types. No SARS‐CoV‐2 DDTE occurred in this interval. Conclusions: Transplantation of SARS‐CoV‐2 NAT+ donor organs appears safe for short‐term outcomes of death and graft loss and ameliorates the organ shortage. Further study is required to assure comparable longer term outcomes. Abstract :